1979
DOI: 10.1111/j.1365-3059.1979.tb02626.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival of sclerotia of Rhizoctonia tuliparum

Abstract: SUMMARY In 1974 a severe outbreak of grey bulb rot (Rhizoctonia tuliparum Whetzel & Arthur) occurred on tulips in Lincolnshire in a field not planted with a highly susceptible crop for six years. A long‐term experiment on the survival of R. tuliparum showed that about 10 per cent of sclerotia can remain viable for at least 10 years. Where severe outbreaks of disease have occurred, longer intervals between susceptible crops are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…They found that the proportion of sclerotia germinating following retrieval from field soil was 45% in the top 1 cm of soil, 19% between 1 and 5 cm from the soil surface and 6% between 15 and 20 cm. For another Rhizoctonia sp., R. tuliparum, 25 and 36% of sclerotia retrieved from 0 and 7.5 cm depth were viable after 7 years, compared to 9 and 29% at 15-to 22.5-cm depth (Coley-Smith et al 1979).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…They found that the proportion of sclerotia germinating following retrieval from field soil was 45% in the top 1 cm of soil, 19% between 1 and 5 cm from the soil surface and 6% between 15 and 20 cm. For another Rhizoctonia sp., R. tuliparum, 25 and 36% of sclerotia retrieved from 0 and 7.5 cm depth were viable after 7 years, compared to 9 and 29% at 15-to 22.5-cm depth (Coley-Smith et al 1979).…”
Section: Discussionmentioning
confidence: 88%
“…Sclerotia produced by Rhizoctonia tuliparum were found to survive burial for over 10 years, although the percentage of sclerotia germination following retrieval was <10% (Coley‐Smith et al. ). Sclerotial survival in other anastomosis groups of R. solani has also been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They turn from white to dark brown or black as they ripen and can be found on bulbs and in surrounding soil. According to Coley-Smith et al [10], about 10% of the sclerotia can remain viable in soil for at least ten years. Sclerotia usually remain attached to soil and plant debris when the bulbs are dug, allowing them to be easily spread from field to field by cultivating equipment.…”
Section: Introductionmentioning
confidence: 99%